The impact of policy changes: The opportunities of Community Renewable Energy projects in the UK and the barriers they face. (June 2019) - Mirzania, Pegah; Ford, Andy; Andrews, Deborah; Ofori, George; Maidment, Graeme
Abstract: The UK's energy system is predominantly centralised with a major reliance on fossil fuels. The trilemma of successfully delivering energy security, equity, and environmental sustainability, whilst dealing with an ageing energy infrastructure, demands change within the entire energy system. In recent years, Community Renewable Energy (CRE) projects have played a significant role in the transition of the UK's energy system, but since 2016 government support for them has been less robust. This paper reports a web-based survey and semi-structured interviews of the UK's community energy groups undertaken between August 2016 and March 2017. The results indicate that huge problems have arisen due to the changes in government policy, particularly for solar photovoltaic schemes. The majority of CRE organisations have chosen to focus on managing their existing assets rather than plan further growth. Additionally, this paper highlights the key challenges facing CRE projects that wish to develop innovative business models under the new policy conditions. Highlights: Post-2015 renewable energy policy changes have been detrimental to CRE1 groups. The majority of CRE groups have chosen stagnation under the new policy conditions. Implementing battery storage can overcome the challenges facing the CRE sector in the future. A lack of resources and policy support are main challenges to business model innovation.